Systematic review and meta-analysis: the association between newer-generation antidepressants and insomnia in children and adolescents with major depressive disorder : meta-analysis - Türkmen, Cagdas; Machunze, Noah; Lee, Alycia; Bougelet, Emilie; Ludin, Nicola M.; de Cates, Angharad N.; Vollstädt-Klein, Sabine; Bach, Patrick; Kiefer, Falk; Burdzovic Andreas, Jasmina; Kamphuis, Jeanine; Schoevers, Robert A.; et al. (Journal of the American Academy of Child and Adolescent Psychiatry, 2025)
Objective - To examine the association between newer generation antidepressants and insomnia as an adverse event (AE) in the treatment of children and adolescents with major depressive disorder (MDD). - Method - A systematic search was performed in major databases (inception to August 31, 2023) to retrieve double-blind, placebo-controlled, randomized controlled trials (RCTs) evaluating the safety of 19 antidepressants in the acute treatment (initial 6-12 weeks) of children and adolescents ≤18 years of age with MDD (primary analyses). RCTs in anxiety disorders and obsessive-compulsive disorder (OCD) were retrieved from a recent meta-analysis and included in complementary analyses. A mixed-effects logistic regression model was used to compare the frequency of insomnia in the antidepressant relative to the placebo group. Risk of bias was evaluated using the Cochrane Risk of Bias 2 tool. - Results - In total, 20 trials in MDD (N = 5,357) and 8 trials in anxiety disorders and OCD (N = 1,271) evaluating selective serotonin reuptake inhibitors (SSRIs) or serotonin-norepinephrine reuptake inhibitors (SNRIs) were included. In MDD, antidepressant treatment was associated with a modest increase in the odds of insomnia compared with placebo (odds ratio [OR] = 1.65, 95% CI = 1.21-2.27, p = .002), with no significant difference between SSRIs and SNRIs. The RCTs showed low risk of bias or minor concerns for the assessment of insomnia. The odds of treatment-emergent insomnia were significantly lower in MDD (OR = 1.62; 95% CI = 1.21-2.15) compared to anxiety disorders and OCD (OR = 2.89; 95% CI = 1.83-4.57) for treatment with SSRIs (p = .03). Among individual antidepressants with evidence from ≥3 studies, sertraline had the highest OR (3.45; 95% CI = 1.91-6.24), whereas duloxetine had the lowest OR (1.38; 95% CI = 0.79-2.43). - Conclusion - Children and adolescents are at a modestly increased risk for experiencing insomnia during the first 6 to 12 weeks of treatment with SSRIs and SNRIs. Antidepressant- and disorder-specific variability in the risk of treatment-emergent insomnia may be relevant to consider in clinical decision making. - Plain language summary - This systematic review and meta-analysis examined insomnia as a side effect of antidepressant treatment using data from 20 studies of children and adolescents with depression (N = 5,357). The authors also included 8 additional studies of children and adolescents with anxiety and obsessive-compulsive disorders (N = 1,271) to investigate the generalizability of the results across different psychiatric disorders. The authors found a modestly increased risk of insomnia during the first 6 to 12 weeks of treatment compared to placebo, affecting about 6 out of every 100 young people with depression. The risk of insomnia as a side effect of commonly prescribed antidepressants, namely selective serotonin reuptake inhibitors (SSRIs), was significantly higher in children and adolescents with anxiety and obsessive-compulsive disorders than in those with depression. - Study registration information - The association between newer generation antidepressants and insomnia in children and adolescents with major depressive disorder: a meta-analysis of randomized controlled trials; https://www.crd.york.ac.uk/PROSPERO/view/CRD42023330506